Whistleblowing and Compliance in the Judicial Hierarchy. Issue 4 (3rd April 2014) - Beim, Deborah; Hirsch, Alexander V.; Kastellec, Jonathan P.
<x xml:space="preserve">Abstract</x> One way that principals can overcome the problem of informational asymmetries in hierarchical organizations is to enable whistleblowing. We evaluate how whistleblowing influences compliance in the judicial hierarchy. We present a formal model in which a potential whistleblower may, at some cost, signal noncompliance by a lower court to a higher court. A key insight of the model is that whistleblowing is most informative when it is rare. While the presence of a whistleblower can increase compliance by lower courts, beyond a certain point blowing the whistle is counterproductive and actually reduces compliance. Moreover, a whistleblower who is a "perfect ally" of the higher court (in terms of preferences) blows the whistle too often. Our model shows an important connection between the frequency of whistleblowing and the effectiveness of whistleblowing as a threat to induce compliance in hierarchical organizations.